Strengthening Social Accountability for Better Maternal Health Outcomes in Nepal : DOI: https://doi.org/10.46405/ejms.v6i9.533 - Nepal, Adweeti; Dangol , Santa Kumar (Europasian Journal of Medical Sciences, 2024)
Social accountability (SA) plays a significant role in strengthening health systems to deliver quality healthcare services, particularly in low-middle-income countries. In Nepal, SA approaches in the health sector have principally included citizen charters, social audits, and maternal and perinatal death surveillance and response components. SA has the potential to make a significant contribution to building a robust health system. However, its potential remains far from being realized. In this commentary, we briefly discuss the potentials as well as gaps with respect to the implementations issues concerning the citizen charter, social audit, functionalization of quality assurance committee, Maternal and Perinatal Death Surveillance and Response (MPDSR), and the role ambiguity of federalism. Addressing these barriers and constraints could make SA more effective in improving maternal health in Nepal. In this commentary, we briefly discuss the potentials as well as gaps with respect to the implementations issues concerning the citizen charter, social audit, functionalization of quality assurance committee, Maternal and Perinatal Death Surveillance and Response (MPDSR), and the role ambiguity of federalism. Addressing these barriers and constraints could make SA more effective in improving maternal health in Nepal.